TASLAMPOT (Tanaman Hias Dalam Pot) Pembudidayaan Tanaman Hias Dimasa Pandemi Covid 19 - Ragil; Afif; Risal; Okida Putra; Karlstaine Baginda Soaloon; Abdul Rahman (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
The need for ornamental plants has increased. In addition to the fresh impression, the presence of ornamental plants can nourish the body because existing plants release the oxygen needed by humans. Ornamental plants play a role in producing oxygen and decorate the house or yard where we live, but efficacious medicine for the health of the human body. Taslampot can use the place in the form of plastic pots and clay pots. Taslampot planting media certainly has advantages and disadvantages. The advantages of taslampot, which is practical, do not require a lot of media and the price is relatively cheap. The downside, namely the number and types of ornamental plants that can be accommodated is limited. Taslampot can be used as a practical solution in the limitations of agricultural land. Land limitations do not stop one's intention to cultivate. Some housewives still do the hobby of gardening even though the available space is not large enough.